PARTISIPASI MASYARAKAT DALAM PELESTARIAN LINGKUNGAN PARAWISATA TAMAN LAUT OLELE (DESA OLELE, KABILA BONE) - Rahmawaty Tomayahu; Funco Tanipu; Rudy Harold (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study aims to analyze community participation in the preservation of the tourism environment in Olele Marine Park, Bone Bolango Regency, through the lens of Emile Durkheim's concept of organic solidarity. The research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, and then analyzed to understand the forms of participation as well as their implications for social cohesion within the community. The findings reveal that community participation in preserving the Olele tourism environment is manifested in various forms, such as maintaining beach cleanliness, complying with fishing zone regulations, conserving coral reefs, attending village meetings and socialization activities, and developing local handicrafts to support the tourism sector. The conclusion of this study emphasizes that organic solidarity serves as the foundation of social cohesion in Olele society. The differences in roles between the community, village government, and tourism stakeholders further strengthen social integration, as each party performs different yet interdependent functions to achieve the shared goal of sustaining ecotourism in Olele Marine Park.